2015
DOI: 10.1186/s40781-015-0064-2
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Hassall’s corpuscles in Nandanam chicken - light and electronmicroscopic perspective (Gallus domesticus)

Abstract: The present study was aimed to study the light and electron microscopic studies of thymic Hassall’s corpuscles was done in various age groups of Nandanam Chicken ranging from day-old to forty weeks. Hassall’s corpuscles are special, unique structures present in thymic medulla and also in the cortex of all the age groups of Nandanam chicken (from hatch to forty weeks) in the present study. Size of the Hassall’s corpuscles in the medulla is larger than the ones present in the cortical region of thymus. The Hassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
3
5
0
4
Order By: Relevance
“…It was observed that, group of cyst coalesced to form the larger cysts (Fig 6 and 7). These observations are in agreement with the findings reported by Kannan et al (2015) in fowl. Hashimoto and Sugimura (1976) in Pekin duck reported the similar morphology of cyst.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It was observed that, group of cyst coalesced to form the larger cysts (Fig 6 and 7). These observations are in agreement with the findings reported by Kannan et al (2015) in fowl. Hashimoto and Sugimura (1976) in Pekin duck reported the similar morphology of cyst.…”
Section: Resultssupporting
confidence: 94%
“…These observations of the present findings are in line with reports made by Kannan et al (2015) in fowl, Gulmez and Aslan (1999) in Geese, Tamilselvan et al (2017) in Guinea fowl, Hashimoto and Sugimura (1976) in Pekin duck and Senapati et al (2015) in quail, chicken and duck. Th ese work ers repo rted the sim ilar morphology of Hassall's corpuscles.…”
Section: Resultssupporting
confidence: 93%
“…In addition to the conventional mTECs described above, the thymic medulla contains unique structures called Hassall’s corpuscles (HCs). These structures, firstly characterized in 1846 by Arthur Hill Hassall ( 38 ) in human thymi have, after their initial description, been found in several other mammals ( 39 ) but as well as in bird and fish species ( 40 , 41 ). In humans, the HCs appear as a concentric merged cluster of unnucleated cells with a typical diameter of 20-100 μm and are present in large quantities already by the 28 th week of prenatal development ( 42 ).…”
Section: The Aire+ Mtecs Post-aire Mtecs and Hassall’s Corpusclesmentioning
confidence: 95%
“…The spleen is the largest secondary lymphoid organ in mammals and also the primary site for proliferation and differentiation of immune cells and has been described as a center of blood filtration [4]. The splenic parenchyma has a crucial role in immune responses such as exposure to antigens transmitted by blood according to studies by [10].…”
Section: Introductionmentioning
confidence: 99%